Pembatalan Hibah Oleh Orang Tua terhadap Anak Berdasarkan : Studi Kasus Putusan Nomor 100/PDT.G/2024/PN SKT - Muhammad Arif Triyoga; Ryan Adhi Pratama; Gholib Sindhu Pratama; Hafidz Lukman Hakim; Syafrizal Aldi Tursandi; Universitas Tidar (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This article discusses the Cancellation of Grants by Parents to Children Based on a case study of decision Number 100/Pdt.G/2024/PN Skt., this study analyzes the legal consequences of the cancellation of grants made between parents and their biological children. A grant is a type of unilateral agreement that is free and basically cannot be canceled, except under certain conditions as regulated in Article 1688 of the Civil Code and Article 212 of the Compilation of Islamic Law. If related to the problems in the decision, then Ms. Mar Intan gave a grant to her child, R Akun Rumawas, through a valid notary deed. However, the problem arose when there was an alleged intervention by a third party, namely (Mrs. Handariningsih) who influenced the free will of the grantor, causing the agreement to be flawed. The normative legal method and qualitative approach were used in this study. Court decisions were evaluated using qualitative methods. This study shows that intervention by a third party that causes a discrepancy in will can be a reason for the court to cancel a grant, even though the grant was made according to procedure. This result emphasizes how important it is to maintain the will of freedom in providing grants in accordance with legal regulations in every legal act of grants to ensure justice and legal stability so that it can provide certainty, justice and legal benefits for the community.